THE ESSENCE OF INDEPENDENCE CHARACTER EDUCATION FOR EARLY CHILDHOOD ACCORDING ISLAMIC PERSPECTIVE - Zulkhaidir, Zulkhaidir (Tawazun: Jurnal Pendidikan Islam, 2018)
The independence of character education for early childhood should receive serious attention by all parties concerned with the development of children of early childhood. Government, teachers and parents have to exactly understand what the objectives of independence of character education for the early childhood. How is the method used as a support in order to achieve the target so that children grow and develop into independently according to their age. The Healthy children, the comfort physical environment, the availability of educational games. The balance of children social environment, The parents who are proficient in assisting children in finding solutions that are being faced by them, as well as parents who put the realistic goal of education, Those are the main asset in realizing independence early childhood. Islam has actually laid the foundations of early childhood education long before the child was born. As an example, a man and women who want to marry in order to pay attention to the quality of morals and religion of their candidates. Someone who understood the teachings of religion will certainly devote all responsibilities for the wife and the children's education as early as possible, including a self-taught character as has been taught by the Prophet. Keywords : independence education, early childhood, Islam